ANALISIS KEPUASAN MAHASISWA MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS DAN CUSTOMER SATISFACTION INDEX - I Putu Pranatha Sentosa; Ni Made Erpia Ordani Astuti; I Made Elia Cahaya (LPPM Universitas Dhyana Pura, 2019)
ABSTRACT The purpose of this study was to determine the level of importance of each attribute by Importance Performance Analysis (IPA) and know the level of customer satisfaction based methods Customer Satisfaction Index (CSI). This study uses SERVQUAL instrument. Based on the Cartesian diagram, the attributes that go in the first quadrant is an attribute whose performance needs to be improved and to be evaluated every month in order to determine the wishes of the consumer. Attributes included in quadrant II are the attributes that need to be maintained and its performance has been satisfactory consumer. Attributes included in quadrant III is an attribute that has a low priority and the quadrant IV are the attributes that are considered less important by customers but the performance has been very good restaurant. The results showed that the overall level of customer satisfaction (based on the value CSI) of 81.83% and is located in a range of values from 81.00%-100% indicating that visitor satisfaction index is the criterion of